Tinjauan Buku: Iman, Pengharapan dan Kasih - L M, Yusuf (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
The Christian way of life is a life that must of course be based on faith. That faith is based on belief in Jesus Christ who died and rose and ascended to Heaven. This faith then produces hope for everyone who believes in Christ, namely that they will definitely have eternal life. In this hope, believers are strengthened to remain faithful and live to carry out God's will. They are the ones who can enjoy eternity amidst the temporary nature of this world. In the end, with the Faith and Hope they have, believers can share love with each other. This love certainly comes from the Triune God. This is what pleases and glorifies God in the life of a Christian. This book explicitly and comprehensively explains to believers that aspects of loyalty, honesty, sincerity and holiness of life in following Jesus Christ can only be achieved correctly if they hear God's Word and then examine it correctly. So Faith, Hope and Love significantly emerge in the life of the congregation as a whole.